ISOLATION AND CHARACTERIZATION OF THERMOSTABLE RECOMBINANT SERINE HYSROXYMETHYLTRANSFERASE FOR ?-HYDROXY AMINO ACIDS BIOSYNTHESIS - Fauziah Ma'ruf, Ilma
Serine hydroxymethyltransferase (SHMT) is one of the enzymes belonging to the PLP-dependent enzyme. SHMT is multifunction enzyme catalyzing various reactions involving a few ?-hydroxy amino acids (serine, threonine and phenylserine). Currently the production of L-serine and L-threonine depends on fermentation using Escherichia coli or Clostridium glutamicum. However, the use of whole cell biocatalyst has several weakness. Therefore, study of the biosynthesis of ?-hydroxy amino acids with an enzymatic approach using SHMT is very interesting to be conducted. The characteristics of enzymes used in industry usually have high activity and stability and use high concentrations of substrates. Thermostable enzyme or the gene was isolated from microorganisms living at high temperature environments. the goal of the research is to obtain recombinant SHMT which has an activity for the synthesis of various ?-hydroxy amino acids. To achieve the above goal, isolation of gene encoding SHMT (glyA) has been carried out. SHMT protein was expressed using E. coli Rosetta 2 (DE3), isolated and purified using the NiNTA affinity chromatography method. The pure enzyme was characterized using a retro-aldol cleavage reaction. In addition, the ability of enzymes to synthesize various ?-hydroxy amino acids using aldol condensation reactions has been investigated.Cloning of SHMT local isolates (ITBSHMT_1, ITBSHMT_2 and ITBSHMT_3) were successfully carried out. ITBSHMT_1 and ITBSHMT_2 were isolated from bacterial isolates originating from thermogenic phase compost, the two SHMTs had the highest similarity with Pseudoxanthomonas taiwanensis SHMT. While ITBSHMT_3 was isolated from the metagenome sample from Kawah Domas, the gene sequence of this SHMT has the highest similarity to Metallosphaera sedula SHMT. Bioinformatics characterization was carried out for the three SHMTs and compared with 2 different SHMT isolates from Japan (Synthetic Bioengineering Laboratory, Osaka University), namely Ta0811 and Ta1509 from Thermoplasma acidophilum. Alignment of the 2-dimensional structure with the well-characterized SHMTs and superimposition of the 3-dimensional model structure with the crystallized SHMT structure, shows that ITBSHMT_1 and Ta0811 have novel structural characteristics, the presence of an additional fragment (VSRQG) near the PLP binding site on ITBSHMT_1 and the absence fragment of the THF binding loop on Ta0811. The recombinant proteins of ITBSHMT_1 and ITBSHMT_2 are produced using host cells E. coli Rosetta 2 (DE3) in an active form however ITBSHMT_3 wass expressed in the form of an inclusion body (IB) as occurs in Ta1509 from T. Acidophilum which both have a molecular weight of around 48,1 kDa. The characterization showed that ITBSHMT_1 has optimum activity at 80 ?C. This enzyme has an optimum pH on 7.5 and thermal stability up to 60 ?C. The data suggested that the thermal stability of the enzyme follows the optimum temperature for the growth of the original microorganism (P. taiwanensis), which is around 55 ?C. Another characterization of ITBSHMT_1 shows the influence of transition metals (Mn2+, Ni2+, Zn2+, Cu2+ and Co2+) which significantly reduces enzyme activity. On the other hand, alkaline earth metals (Mg2+, Ca2+), alkali metals (Na+ and K+) and chelating agents (EDTA) have no effect on enzyme activity like the other SHMTs that have been characterized, this result suggested that SHMT is nonmetalloenzyme. On the other hand, the activity of the enzyme is enhanced by the presence of a reducing agent (?-mercaptoethanol). Kinetic parameter showed that ITBSHMT_1 had better phenyilserine retro-aldol cleavage catalytic efficiency than SHMT from psychrophilic (Psychromonas ingrahamii) and mesophilic (E. coli) bacteria with catalytic efficiency values of 8, 0.826 and 0.146/s respectively. The enzyme has specific activity for retro-aldol cleavage reactions in the following order: DL-phenylserine>L-allo-threonine>L-serine. The synthesis of ?-hydroxy amino acids showed that ITBSHMT_1 showed an activity for the synthesis of serine, threonine and phenylserine with the following specific activities: serine> threonine> phenylserine. Optimization of serine production using ITBSHMT_1 showed that THF concentration of 2 mM was sufficient to produce maximum yield and enzymes with the same number of units were able to catalyze substrates with varying concentrations (50, 200 and 400 mM) with % conversion of around 70–75%. Assay for L-serine synthesis using resting cell E. coli expressing ITBSHMT_1 showed that this enzyme has a better rate of L-serine synthesis compared to SHMT from the mesophilic group. All of the results suggest that ITBSHMT_1 is good candidate of enzyme to be used in industry since it showed thermostability, fast reaction rates and convert substrates in high concentrations (400 mM).